Physical and Mechanical Properties of Sheepskin Pickled by Recycled Curing Salt - Awoke Fenta Wodag; Girmaw Yeshanbel Kefale (Journal of Engineering)
Curing is the first process of skin treatment mainly using sodium chloride salt to prevent its decay. At soaking step of tannery, the effluents will be discharged to the environment, which contains the chloride ion, which will negatively affect our environment. Therefore, it should be either treated or reused so that it can help to reduce amount of chloride ion of the soaking effluent discharged to the environment and cost of pickling. This study focused on recycling of curing salt for sheepskin pickling and studying its effect on the pickled skin’s properties. Salt was recycled from cured skins manually, and it was purified through dilution, filtration, treatment, and drying. Five enzymatic bated sheepskins were collected from Bahir Dar, Ethiopia. The recipes were developed based on the weight of the pelt which was going to be pickled with 0.8% H2SO4, 0.5% formic acid, and 80% H2O for each trial and the recycled salt at different concentrations (8%, 8.5%, 6.5%, 7%, and 7.5%) for S1, S2, S3, S4, and S5, respectively. Bromocresol green was the pH indicator. Then, properties of treated samples were measured and evaluated in line with ISO standards, and the pH of the recipe was checked. The results showed that S1 treated with the mentioned materials and 8% salt amount has highest tensile strength (80.3 N/mm2). In addition, S1 has also the maximum tear strength of 60 N/mm2 and the minimum was 45.69 N/mm2. On the contrary, S3 has shown the least values of tensile strength and elongations as well as least tear strength. S1 has the maximum shrinkage temprature of 107°C and S3 has that of the least value 89°C which is lower compared with the standard shrinkage temperature, 95°C. The pH values were found to be within the standard for pickling. The overall result of this study was promising.